PERJANJIAN PERKAWINAN DALAM PERKAWINAN PADA GELAHANG - Mantra, I Gede; Januariawan, I Gede; Yanti, Ni Putu Linda Mega (Institut Hindu Dharma Negeri Denpasar, 2020)
Marriage â€œpada gelahangâ€ is an alternative form of marriage chosen by both parties of the prospective husband and family, considering that both the male family and the family of the woman are basically equally an only child.This type of research in this study is a type of normative hokum research or doctrinal research namely